Cost-effectiveness of molar single-implant versus fixed dental prosthesis - Arai Korenori; Kawakami Koji; Teranishi Yuki; Tatsunori Murata; Tanaka-Mizuno Sachiko; Baba Shunsuke (BMC, 2018)
Abstract Background This study evaluates the cost-effectiveness of implants (Implant), insurance fixed dental prosthesis (IFDP) and private fixed dental prosthesis (PFDP) for a single intermediate missing tooth in the molar region to calculate the Incremental Cost Effectiveness Ratio (ICER). Methods The Markov model for cost-effectiveness analysis of the Implant, IFDP and PFDP was carried over maximum 30 years. The starting age for prosthetic treatment was decided to be 50 years. The General Oral Health Assessment Index (GOHAI) was used for the indicator of effectiveness as an oral health QOL value. The GOHAI value was collected from patients who visited the Department of Oral Implantology of Osaka Dental University between September 2014 and March 2016. In addition, the Tornado diagram was drawn and Monte-Carlo simulations made for sensitivity analysis. Results From the analysis of survey of QOL of each stage and treatment, the selection of an Implant led to a higher QOL value than FDP. However, the estimated 30-year cost for IFDP was lower than Implant. It also became evident that PFDP had an extended dominated condition compared with IFDP and Implants. The ICER on the Implant versus IFDP was €1423.00. Conclusions These results suggest that a better of QOL value can be obtained from an Implant than from IFDP or PFDP. An evaluation form using an indexed scale for oral health-related aspects needs to be developed that is also consistent as an indicator of effect.